SURFACE COATING OF ACRYLATE POLYMER ON SENGON WOOD (Paraserianthes falcataria L. NIELSEN) USING UV IRRADIATION - Darsono Darsono; Sudrajat Iskandar (Jurnal Sains Materi Indonesia, 2014)
SURFACE COATING OF ACRYLATE POLYMER ON SENGON WOOD (Paraserianthes falcataria L. NIELSEN) USING UV IRRADIATION. An experiment on surface coating of sengon wood (Paraserianthes falcataria L. Nielsen) using ultraviolet (UV) irradiation has been conducted. Epoxy acrylate and urethane acrylate resins were used as coating materials after addition of tripropylene glycol diacrylate and a photoinisiator, Darrocure 1173. Irradiation was conducted using UV light at the conveyor speed of 2, 3, 4, and 5 m/minutes. Parameters observed were glossyness, adhesion, hardness, abrasion resistance and chemical, solvent and stain resistance. The superior results of the epoxy acrylate films were obtained to show excellent adhesion on the surface of wood meeting with the standard because of greater remaining values than 50 % (ASTM 2571-71), together with the high degrees of abrasion, hardness, glossyness and torelance against chemicals, solvent, and stain except against 10 % NaOH solution.